PERBEDAAN KUALITAS HIDUP PADA PASIEN ASMA RAWAT JALAN YANG LEBIH PATUH DAN KURANG PATUH PADA PENGGUNAAN OBAT ASMA INHALASI - , Qurrata A'yun ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Failure to adhere to drug regimen can increase morbidity and mortality. While Medication Adherence Report Scale for Asthma (MARS-A-10) is a specific psychometric to measure adherence to a regimen of inhaled asthma medications, Asthma Quality of Life Questionnaire (AQLQ) measures quality of life. The average difference of 0.5 points per item per domain of total score for each intervention illustrates the difference in minimal clinically important difference (MCID). This study aims to verify whether patients who fail to adhere to the regimen have quality of life scores 0.5 points lower than those who strictly adhere to a regimen of inhaled asthma medication. Subjects of the study are patients at Poliklinik Paru of Sardjito Hospital and Poliklinik Penyakit Dalam Sleman General Hospital, Yogyakarta. The study also attempts to reveal factors other than adherence to drug regimen that may affect quality of life. Since the study is cross-sectional, it makes the most of data gathered from a survey on adult asthma patients at Poliklinik Paru of Sardjito Hospital and Poliklinik Penyakit Dalam Sleman General Hospital, Yogyakarta. The independent variable in the study is adherence to a drug regimen which is measured using MARS-A-10 modified with Visual Analogue Scale (VAS) as a response to answer for each item. Adherence scores range from 0-900 with a cut point at <810 which will be considered as failure to strictly adhere. The difference in AQLQ score of 0.5 points, a clinically significant value, becomes the minimum value separating patients who adhere to drug regime less strictly and those who adhere more strictly to the regimen of inhaled asthma medication. Multivariate regression analysis is used to identify variables that demonstrate a statistically significant relationship with the AQLQ as the dependent variable. Stepwise method is used to remove variables with p values less than 0.5. There are 53 subjects of the study, 36 of whom are women, the mean age is 49.26 ± 10.64 years (mean ± SD), mean disease duration is 21.15 ± 13.51 years with asthma (mean ± SD), the mean time use of inhaled asthma medication is 9.09 ± 6.51 years (mean ± SD). The mean adherence score is 600.99 ± 173.40, with 84.9% of them adhere to drug regimen less strictly (score <810). The average difference in AQLQ total score between those who adhere to drug regimen less strictly and those who adhere more strictly is 0.67 points. The multivariate analysis model consisting of adherence as independent variables and three confounding variables (medical record concerning treatment in ICU, the level of asthma control and how long the patient is on inhaled asthma medication) produces R2 of 0.445. Better quality of life is closely associated with better asthma control, minimum incidence of hospitalization in the ICU, duration of inhaled asthma medication use, and high score of adherence to the drug regimen.